THE EFFECT OF THINK PAIR SHARE IN ONLINE CLASS TOWARDS STUDENTS’ READING COMPREHENSION - Mohammad Ihsan Hidayat; Putri Asilestari (Journal of English Language and Education, 2021)
This research aims to find out whether there were an effect on using Think Pair Share as a media towards the students’ readingcomprehehnsion in online class, in academic year 2019/2020. This research was quasi-experimental research that carried out at tenth grade students of SMAN 1 Kuok. It involved 48 students of two classes, X IPA as experimental class and X IPS as control class. Each class consisted of 24 students. The experimental class was taught by using Think Pair Share while control class was taught byusingConventional method. The data were analyzed by using T-test formula.Thedata shows that the significant (2-tailed) was 0.000 smaller than 0.05. It can be concluded that the post-test score in experimental class have an effect toward the students’ reading comprehension. It means there is a significant difference in the reading comprehension between the students who were taught by using Think Pair Share and those who were taught by using Conventional method. Based on the result findings, it can be concluded that the use of Think Pair Share in teaching reading comprehension in online class was effective.